Theory of cultivation in Korean drama in social media - Adawiyah, Sa'diyah El; Patrianti, Tria; Hermanto, Agus; Ginting, Rahmanita (Interaksi: Jurnal Ilmu Komunikasi, 2025)
Social media (paid) as a medium to meet the information needs of Korean entertainment shows which are very limited can be watched through Indonesian television media. Of course, this does not rule out the transmission of foreign cultural values and norms that colour and influence the culture of the society in Indonesia. This research aim is to determine what kind of contribution or affect the transmission of Korean culture includes cognitive, affective and behavioural aspects. The method used in this research is descriptive. The technique of collecting data through interviews with informants uses a purposive sampling technique, which is where informants are selected with specific considerations and goals and based on their accessibility by the researcher. The results of this study indicate that there is a process of transmission of Korean popular culture that contributes to the impact of acceptance on the audience from cognitive, affective to conative or behavioural aspects. Among them include, increasing knowledge and understanding, generating interest and changing views, as well as imitating, identifying, and adopting behaviour in terms of imitation and identification theory. This study concludes that the transmission of Korean culture such as Korean drama through social media contributes to the impact of acceptance on the audience, from cognitive, affective to conative or behavioural aspects.